Altered plasma and erythrocyte phospholipid fatty acid profile in elite female water polo and football players - Arsic, A.; Vucic, V.; Tepšic, J.; Mazic, S.; Djelic, M.; Glibetic, M. (Applied Physiology, Nutrition, and Metabolism, 2012)
The impact of chronic, intense exercise, such as in elite athletes, on phospholipids fatty acids (FA) composition has not been studied in women so far. This study aimed to investigate FA profiles in plasma and erythrocytes phospholipids in elite female water polo (N = 15) and football (N = 19) players in comparison with sedentary women. In spite of similar dietary patterns, as assessed by a food frequency questionnaire, plasma FA profile in the football players showed significantly higher proportions of stearic acid, oleic acid, and monounsaturated FA (MUFA), and significantly lower proportions of total and n-6 polyunsaturated FA (PUFA) than in the water polo and control group. The water polo players had higher percentages of palmitoleic acid and arachidonic acid than the control subjects. Erythrocyte FA profile differed among groups. We found significantly higher proportion of oleic acid and MUFA in the football group than in the controls, and decreased stearic acid and elevated palmitic and palmitoleic acid in the water polo players than in the other 2 groups. Both groups of athletes had significantly lower percentages of n-6 dihomo-?-linolenic acid, n-6 PUFA, and total PUFA compared with the controls. The estimated activities of elongase and desaturases in erythrocytes were also altered in the athletes. Our results indicate that long-term, intense physical training significantly affects FA status of plasma and erythrocyte phospholipids in women. The observed differences between the water polo and the football players suggest that the type of regular training may contribute to the altered metabolism of FA, although possible genetic differences among the 3 study groups cannot be ruled out.